The Effectiveness of inulin on health status, digestive activity, and production of common carp Cyprinus carpio - Gurning, Putri Sartika; Nikhlani, Andi; Agustina, Agustina; Pagoray, Henny; Maidie, Asfie; Fitriyana, Fitriyana (Jurnal Akuakultur Indonesia, 2025)
The addition of inulin to fish diets has the potential to enhance health, growth performance and feed utilization. This study aims to evaluate the role of inulin on the health status, digestive activity, and production levels of common carp (Cyprinus carpio) in farming. This study employed a completely randomized design with four treatments and three replications, consisting of diets with 0, 2, 4, and 6 g/kg of inulin diet. The study involved 120 fish, with each group containing 10 fish weighing 8.46 ± 0.42 g was reared in each 30 L aquarium for 30 days. Fish were fed according to the treatment, at satiation twice daily. Hematology parameters showed normal ranges and intestinal histology revealed an increase in intestinal villi size with the addition of inulin. The treatment with inulin at 4 g/kg diet showed highest number of lactic acid bacteria in the fish intestines (P